EFFORTS THE CLIMATE CHANGE MITIGATION AND ADAPTATION: THE CONTRIBUTIONS OF TORO COMMUNITIES IN LORE LINDU NATIONAL PARK - Golar Golar; Hasriani Muis; Abdul Rosyid; Wahyu Syahputra Simorangkir (Forestry Study Program University Of Mataram, 2023)
In the last few decades, the global temperature increase is something society cannot avoid. Thus, each country's international policies at COP 26 deal with this phenomenon. Among these international policies to minimize the temperature rise that has occurred, are the presence of non-party-stakeholders, one of them indigenous peoples with a variety of local knowledge in maintaining the sustainability of forest ecosystems. In case of that, this study discusses efforts for the climate change mitigation and adaptation of Toro customary communities in Lore Lindu National Park. This study used a qualitative descriptive approach with a Delphi study. The results of our study show the effort of Toro communities to mitigate and adapt the climate change divided by the Nature School of Ngata Toro, Ombo, and the advantage of the land space of the forest. The development of these three patterns would greatly benefit Indonesia's program policy (FoLU Net Sink 2030). In order for the community to be aware of the values of local wisdom that may be applied in forest management in order to mitigate climate change, LLNP as the owner of a conservation area surrounding the forest, must be able to translate this potential efficiently.